A cross-sectional study on BMI and eating habits among students in a medical college in Kerala - Amruth, M.; Kumar, Akshath (International Journal Of Community Medicine And Public Health, 2019)
Background: Obesity and overweight is increasing nowadays among the medical students. Erratic eating habits and other lifestyle related risk factors are mainly implicated for this increasing burden, and research related to these risk factors is essential, considering their role as future physicians and role models in public health intervention programs. The present study was conducted to estimate the BMI values of medical students and to compare obesity among male and female students with their socio-demographic factors, eating habits and lifestyle. Methods: A cross-sectional study was conducted among medical students in a medical college in Kerala during 1st May 2018 to 30th July 2018. A total of 573 students out of 600 participated in the study. Using a structured questionnaire data was collected. BMI was calculated for 483 medical students with age group of 20 years and above including 173 males and 310 females. SPSS version 17 was used for statistical analysis. Results: Using WHO BMI classification 18.2% were overweight and 2.1% were obese. Using Asia- Pacific BMI classification 18.2% were overweight and 20.3% were obese. Male students were more obese than females. Skipping breakfast, eating full stomach, not knowing balanced nutrition, eating fatty foods and snacks, eating more under stress and drinking soft drinks were common unhealthy eating habits among obese students. Conclusions: Obesity and overweight is very prevalent among medical students. Improving their knowledge regarding balanced nutrition, regular eating habits, proper stress management and adoption of healthy lifestyle will result in proper body weight and prevent obesity complications.